Solid pseudopapilar neoplasm of the pancreas: experience in a center and review of the literature (Boletin Médico de Postgrado, 2025)
Solid pseudopapillary neoplasm of the pancreas is a rare entity representing 2% to 3% of pancreatic neoplasms and 0.9% to 2.7% of pancreatic neoplasms of exocrine origin. In the original description, the tumor was classified as a benign exocrine glandular lesion, most probably a papillary cystadenoma. We present cases of female patients who presented symptoms such as epigastralgia, nausea, heartburn and dyspepsia with imaging studies suggestive of pseudopapillary neoplasm of the pancreas confirmed by biopsy via FNA, who underwent surgical resection with definitive biopsy and satisfactory evolution. This pathology, although infrequent, is easily diagnosed and its surgical resolution is mandatory. Cephalic duodenopancreatectomy is preferred for those cases in which the lesion is confined to the head of the pancreas, either for its variant in Whipple or Traverso-Longmire surgery as well as its variants in gastric reconstruction; likewise, for those cases in which it is present in the body and tail of the pancreas, corpocaudal pancreatectomy is performed with or without splenic preservation and/or preservation of the splenic vessels.